Thermally stable ultrafine grained copper induced by CrB/CrB2 microparticles with surface nanofeatures via regular casting. (1st December 2020) - Yao, Gongcheng; Cao, Chezheng; Pan, Shuaihang; Yuan, Jie; De Rosa, Igor; Li, Xiaochun
Graphical abstract: Highlights: As-solidified UFG Cu was enabled by microparticles (CrB and CrB2 ) with surface nanofeatures via regular casting. The UFG Cu/CrB and Cu/CrB2 samples exhibit exceptional thermal stability. The substantial grain refinement is attributed to the continuous heterogeneous nucleation and grain growth restriction. The mechanical properties of the Cu/CrB and Cu/CrB2 samples are significantly enhanced over pure Cu. Abstract: Ultrafine-grained (UFG)/nanocrystalline materials possess novel properties. Refining as-solidified grains of metals to the ultrafine and even nanometer scale by nanoparticles via slow cooling has been recently discovered. Here, we report that microparticles (CrB and CrB2 ) with surface nanofeatures can also enable ultrafine/nano grains via slow cooling. CrB/CrB2 microparticles, formed by coalescence of nanoparticles in Cu matrix, display surface nanofeatures, which induce substantial grain refinement and stabilization down to the ultrafine/nano scale. The UFG Cu/CrB and Cu/CrB2 samples exhibit exceptional thermal stability, comparable to UFG Cu induced by nanoparticles, without coarsening after annealing at 600 ℃ for 1 h. The microhardness, strengths, and Young's moduli of the Cu/CrB and Cu/CrB2 samples are significantly enhanced over pure Cu. This discovery has great potential to advance the mass production UFG/nanocrystalline for widespread applications.